Mecanismos Legales para la protección ambiental de los bosques urbanos en cuatro municipios de la Provincia de Buenos Aires (Papeles, 2021)
This paper is part of two research projects entitled «Development of tools for urban and peri-urban green infrastructure management in municipalities of Buenos Aires Province» and «Ecosystem services provided by water and urban forests at the Lujan river basin, in Argentina. Contributions from a social, legal and environmental approach» PICT 2019-00713. Urban Forests (UF) as a key component of urban green infrastructure could contribute to the sustainable development of cities to improve the population's quality of life. There are national regulations, such as the Forest Wealth Defense Law (13273), which could contemplate the UF one; buthowever, there is no law that specifically protects the fore mentioned infrastructures at this level. Buenos Aires Province unifies guidelines through the Public Tree Law (12276), delegating to municipalities.